Novel nanoscale phenomena on Si(100). STM and DFT investigation of nanoscale contract and molecular adsorption - Ryan, Peter M. (Trinity College (Dublin, Ireland). School of Chemistry, 2009)
Prompted by the limited information that might be harnessed en route to the rational design of molecular scale electronic devices, the research undertaken within this thesis is concerned with the self assembly mechanisms of molecular scale systems on surfaces and the development of experimental procedures to be employed in the characterisation of such structures. To these ends, chapter 6 presents an ab initio study of the Si(100) surface reconstructions and examines the applicability of certain organic chemistry models to describe reactions on this surface. It is shown, from the ab initio analysis, that the traditional understanding of the simplest of the cycloaddition reactions on this surface is in need of revision. In chapter 7, further results from our ab initio study of the are utilised in order to account for STM observed steroselectivity in the reactions of 1,3 cyclohexadiene and naphthalene on Si(100).
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.